2018
DOI: 10.1016/j.ecoenv.2018.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Gamma irradiation during gametogenesis in young adult zebrafish causes persistent genotoxicity and adverse reproductive effects

Abstract: The biological effects of gamma radiation may exert damage beyond that of the individual through its deleterious effects on reproductive function. Impaired reproductive performance can result in reduced population size over consecutive generations. In a continued effort to investigate reproductive and heritable effects of ionizing radiation, we recently demonstrated adverse effects and genomic instability in progeny of parents exposed to gamma radiation. In the present study, genotoxicity and effects on the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…The dose compares to observations from Chernobyl, where the total accumulated dose over 60 days post-accident was estimated at 10 Gy 49 . These doses did not cause effects on survival in our study on directly exposed adult zebrafish 50 . The swimming space volume was approximately 6 L (16 × 18 × 22 cm) with custom made grids.…”
Section: Methodscontrasting
confidence: 49%
See 1 more Smart Citation
“…The dose compares to observations from Chernobyl, where the total accumulated dose over 60 days post-accident was estimated at 10 Gy 49 . These doses did not cause effects on survival in our study on directly exposed adult zebrafish 50 . The swimming space volume was approximately 6 L (16 × 18 × 22 cm) with custom made grids.…”
Section: Methodscontrasting
confidence: 49%
“…Other overrepresented pathways following gene expression as well as DNA methylation analysis could indicate effects that manifest later in life, such as axonal guidance signalling involved in neurodevelopment, and FSH signalling linked to reproductive outcome. Interestingly, irradiated parents exhibited effects on ovaries with an increase in pre-vitellogenic follicles, indicating effects on maturation of oocytes, which could involve FSH signalling 50 . These results indicate potential novel affected molecular mechanisms in radiation response.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from using zebrafish as an in vivo model system, in addition to the zebrafish embryo model that can be regarded as an in vitro method, the use of zebrafish cultured cell lines in genetic toxicology is also on the rise [91,[97][98][99][100][101]. Up to now there have been more than 100 papers describing the zebrafish model both in vivo and in vitro using the comet assay for the assessment of different physical and/or chemical agents such as gamma rays [102,103], X-rays [104], pesticides [105], insecticides [106], fungicides [88,107], herbicides [108], mycotoxins [109], pharmaceuticals [98,99,[110][111][112], heavy metals A c c e p t e d M a n u s c r i p t 9 [108,113,114], PAHs [89], nanoparticles [115][116][117][118], flame retardants [119], sewage effluent [120], waste material [121] as well as model toxicants such as benzo(a)pyrene (B[a]P), methyl methanesulfonate (MMS) and ethyl methanesulfonate (EMS) [122,123].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Additionally, the histone PTM landscape has been described for this stage [29, 30]. We have recently described effects on the zebrafish embryo transcriptome after 3 h exposure to low dose rates (0.54, 5.4 and 10.9 mGy/h) of gamma radiation [5], as well as the short term and long term effects on the F1 embryo transcriptome after 27 days of parental exposures (8.7 and 53 mGy/h) [31, 32]. These studies also demonstrated adverse reproductive effects and genomic instability in F1 offspring [32].…”
Section: Introductionmentioning
confidence: 99%